2021
DOI: 10.1186/s12909-021-02860-z
|View full text |Cite
|
Sign up to set email alerts
|

E- Learning experience of the medical profession’s college students during COVID-19 pandemic in Saudi Arabia

Abstract: Background Worldwide, most of educational institutions have moved to online electronic learning methods because of the COVID-19 pandemic. On March 8, 2020, the Saudi Ministry of Education announced remote learning for public and private schools and universities as a preventive and precautionary measure to curb the spread of the coronavirus. The objective of this study was to explore the e-learning experience of the students of the colleges of health sciences with regard to the technical prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0
11

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 44 publications
6
30
0
11
Order By: Relevance
“…Although the application of these new methodologies, mainly MOOCs, has its advantages and disadvantages [51,52], these new teaching methods can significantly improve the learning and motivation of our students, also taking into account individualized learning [53,54]. Our results show a high acceptance by the students, according to the results of other authors [25,55]. In fact, interactive videos in the virtual visit case have been shown to improve the acceptance and motivation of veterinary medicine students.…”
Section: Discussionsupporting
confidence: 76%
“…Although the application of these new methodologies, mainly MOOCs, has its advantages and disadvantages [51,52], these new teaching methods can significantly improve the learning and motivation of our students, also taking into account individualized learning [53,54]. Our results show a high acceptance by the students, according to the results of other authors [25,55]. In fact, interactive videos in the virtual visit case have been shown to improve the acceptance and motivation of veterinary medicine students.…”
Section: Discussionsupporting
confidence: 76%
“…Others reported advantages include the ease of sharing educational materials, effective access to study resources, updated learning materials, and flexibility in time and space [55][56][57]. Further studies also mentioned protecting one's health and ensuring the community's safety, saving travel time, exposing one to new forms of learning, keeping up with the original plan of the semester, having extra time for self-study, and easy access to online resources [38,58], as well as the ability to stay at home, continuous access to online materials, the opportunity to learn at one's own pace, and comfortable surroundings [36].…”
Section: Online Remote Learning During the Covid-19 Pandemicmentioning
confidence: 99%
“…Although, Elliott et al (2015) reported increased workload due to more time needed to prepare online teaching materials, our results show otherwise with only 12% of respondents reporting spending relatively more time preparing for online teaching than they would need for face-to-face teaching. This is intuitive as online learning standards for higher education in the KSA were built according to the best standards that include the provision of cuttingedge technology, training and support, and accessibility (Al Zahrani et al, 2021). However, the current system has a room for improvement which could improve students' and staff 's perception and experience as well as the effectiveness of online teaching.…”
Section: Discussionmentioning
confidence: 99%